CULTIVATION OF ZUCCHINI (CUCURBITA PEPO L.) SUBMITTED TO NPK MINERAL FERTILIZATION AND SOIL CONDITIONING BACTERIA - Barbosa, Karen; Biotech Brasil, Green; Theo Gentil, Kevin (Journal of Interdisciplinary Debates, 2021)
Zucchini (Cucurbita pepo L.) has great socioeconomic importance for the Southeast and Center-South regions of Brazil, and can be cultivated throughout the Northeast region, especially in the state of Paraíba, due to its adaptability to the edaphoclimatic conditions of the Paraiba hinterland. The present study aimed to evaluate the growth of gas exchange and the production of the culture of zucchini (Cucurbita pepo L.) submitted to fertilization with NPK and soil conditioning bacteria. The experiment was in randomized blocks, with 10 treatments and 6 repetitions, the treatments corresponded to the combinations of NPK mineral fertilizer with doses of 0%, 50% and 100% of the need for culture and soil conditioning bacteria Azotobarvar® nitrogen fixing bacteria, Phosphatebarvar® bacteria phosphorus solubilizing action and Potabarvar® bacteria with potassium solubilizing action. T1 = Control (without mineral fertilizer and soil conditioning bacteria); T2 = with 100% of the mineral fertilizer recommended for the crop; T3 Azotobarvar® with the addition of 100% PK; T4 = Azotobarvar® with the addition of 50% nitrogen plus 100% PK; T5 = Potabarvar® with the addition of 100% NP; T6 = Potabarvar® with the addition of 50% potassium plus 100% NP; T7 = Phosphatebarvar® with the addition of 100% NK; T8 = Phosphatebarvar® with the addition of 50% phosphorus plus 100% NK; T9 = Azotobarvar®; Potabarvar®; Phosphatebarvar®; T10 = Azotobarvar®; Potabarvar®; Phosphatebarvar® with the addition of 50% NPK. The plants were grown in pots with a capacity of 45 dm3 for 49 days, during this period the plants were evaluated for growth, gas exchange, dry matter accumulation and production. The association of soil conditioning bacteria, with the 50% dose of NPK fertilization, promoted a greater number of fruits, production and height of the zucchini plants when compared to the treatment without inoculation of the bacteria. It was concluded that the highest values obtained for the growth and physiological parameters were observed in the treatments in which soil conditioning bacteria were used via seeds and fertigation.